The Challenge of Accurate Diagnosis of Oral Lichenoid Lesions in Diabetic Patient: A Case Report - Her Basuki Margono; Riani Setiadhi (Jurnal Material Kedokteran Gigi, 2016)
Mercury in amalgam restoration is one of allergen-induced oral lichenoid lesions which resemble oral lichen planus clinically and histopathologically. Thus, an accurate clinical diagnosis is frequently challenging for clinicians, and it is further complicated because similar oral lesions in oral lichenoid lesions can occur as a manifestation of oral lichenoid drug reactions. This case report illustrates the difficulty of an accurate diagnosis of oral lichenoid lesions due to amalgam restorations in type II diabetes mellitus patient. A 59-year-old male patient presented with a 12-month history of oral ulceration and white striations on left lateral tongue, bilateral distribution of white non scrapable plaque-like lesion mixed together with erosion on buccal mucosa adjacent to amalgam restorations on 37 and 47. The patient’s history for any associated skin lesions was negative. The patient had type II diabetes mellitus with inconsistent intake of oral hypoglycemic drugs, and atopy history of house dust mite and shrimp. We initially diagnosed the case as oral lichen planus. Systemic and topical corticosteroids were instituted, but after a month follow-up, all lesions still showed slight improvement. The final diagnosis of oral lichenoid lesions due to amalgam restorations was made following a positive patch test for amalgam. All lesions were gradually resolved in 3-month follow-up after the causative teeth being extracted. Patch test is useful to differentiate between oral lichenoid lesions and oral lichen planus. The treatment of oral lichenoid lesions due to amalgam restorations is simply removal or replacing the offending materials.